Ignacio Álvarez-Ossorio, Siria contemporánea, Madrid, Síntesis, 2009, 223 pp. - Abu-Tarbush, José (El Colegio de México, 2010)
Ignacio Álvarez-Ossorio, Siria contemporánea, Madrid, Síntesis, 2009, 223 pp.